Companionship and Association (Their Status, Significance, and Necessity in Islamic Mysticism) - alireza rezaee seraji (Āfāq-i Dīn, 2011)
One of the most significant requirements for attaining prosperity and human perfection that all divine religions have attended to and all the great men in the world – the prophets, saints, mystics and sages – have sought is the companionship of and association with the great people. Such association has an enormous impact on man’s fate and according to Sufi sages, all the achievements of man are the result of his association with the wise. Unfortunately, at present, most of the human societies that are faced with acute moral crises are oblivious to this fact, while the holy Qur'an and the traditions have been seriously concerned with such companionship; texts on mysticism have paid considerable attention to this point too. This paper aims at examining the status and significance of companionship and association in religious texts and in Islamic mysticism.